PERBANDINGAN POTENSI ANALGETIK EKSTRAK ETANOL DAN AIR UMBI RUMPUT TEKI (Cyperus rotundus L.) TERHADAP TIKUS Sprague Dawley - Rustiani, Erni; Rahminiwati, Min; Mutiara, Tia (-)
The aim of this study is to compare the potential of ethanolic and water extracted of teki grasstuber on   white  male  rat strain Sprague  Dawley  at  two  months of age and ± 200 g of body weight. The rats were divided among four groups. Each group consists of six rats. The  groupswere ethanolic and water extracted  of  teki  grass tuber, positive control group (Paracetamol) and a negative control group (distilled water). Analgesic potency was tested by inducing pain stimuli previously to the animals, in the form of  heat stimuli  by putting it ona hot plate with  the temperature of 55°C. The responses of rats observed were licking and moving or lifting of their legs. Observations  were made for 1 minute, before  and  after  administration  of  pain stimulus at 15, 30, 45  and 60 minute. The results showed that ethanol and  water  extract  at an effective dose of 49 mg / 200 g of BW, gave relatively the same effect as an analgesic or   positive control group. Keywords : analgesic, ethanol and water extract of teki grass tuber, pain